1957
DOI: 10.1071/bi9570426
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Auxins on the Binding of Pectin Methylesterase to Cell Wall Preparations

Abstract: SummaryIt is shown that the plant auxins 3·indolylacetic acid, 2,4-dichlorophenoxyacetic acid, and a·naphthalene acetic acid are effective in binding pectin methylesterase (PME) to cell wall preparations from tobacco pith and tubers of the Jerusalem artichoke.Each auxin has an optimum concentration for activity. The activity curves are consistent with the hypothesis that the auxin binds PME to cell wall receptor sites by an adsorption mechanism which can be described by the Langmuir adsorption isotherm.It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1958
1958
1989
1989

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The pH titrimetric method described previously (Glasziou 1957b) was used with the minor modification that the pH was kept as constant as possible at 7 •0. In addition, a manometric method was developed for assays which required higher sensitivity.…”
Section: (C) Enzyme Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH titrimetric method described previously (Glasziou 1957b) was used with the minor modification that the pH was kept as constant as possible at 7 •0. In addition, a manometric method was developed for assays which required higher sensitivity.…”
Section: (C) Enzyme Assaysmentioning
confidence: 99%
“…Previously it was shown (Glasziou 1957a(Glasziou , 1957b) that the auxins 3-indolylacetic acid (IAA), 2,4-dichlorophenoxyacetic acid (2,4-D), and a-naphthaleneacetic acid (NAA) were effective in binding pectin methylesterase (PME) to cell wall preparations from which the enzyme had been split with strong salt solutions. Each auxin had an optimum activity at about lO-IJM .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent results from studies on Avena coleoptiles (15,16,19) have suggested that the way in which auxin plasticizes walls to permit increased elongation of cells is by affecting the degree of methyl esterification of the pectic materials in the walls. Other authors (8) have inferred from effects of auxin on the binding of pectin methylesterase in the wall that in promoting elongation, auxin acts through pectin. However, it is difficult to imagine how the minute pectic content found here could have significant influence on the physical properties of the walls: hexuronic acid residues, either as pectic substances or as components in non-cellulosic polysaccharide chains, could possibly have a disproportionate effect in plasticizing the wall by occupying strategic positions in the wall structure, but the degree of economy and order in the distribution of these residues required to achieve such a system would appear to be so high as to make it improbable.…”
mentioning
confidence: 99%
“…Recovery in the alkali extraction was 81 % (Fractions 8 plus 9). If it is assumed that the protein (9.5 %) in the original dried wall fragments was lost by hydrolysis and dialysis during the alkali extraction, an assumption that was supported by the lack of nitrogen in Fraction 8 (23, p. 162). When applied to coleoptiles the ammonium oxalate : oxalic acid extraction removed a mixture of polysaceharides which were separated by a sub-fractionation with ethanol-water.…”
mentioning
confidence: 99%
“…PGs produced by plant pathogens can be inactivated in the rotted tissue by compounds formed during the oxidation and polymerization of host polyphenols (447). Plant auxins, like 2,4-dichlorophenoxyacetic, a-naphthylacetic and P-indolylacetic acid, seem to promote the binding of PEs to the cell wall, controlling thereby the saponification of pectic substances of the cell wall and influencing its plasticity ( [420][421][422]. 8 search' %' , No.…”
Section: Addendummentioning
confidence: 99%